Youth unemployment challenge in Africa: what are the drivers? - Baah- Boateng, W. (Economic and Labour Relations Review, 2016)
Youth unemployment remains a major political and socioeconomic challenge in Africa despite the recent strong growth performance of many African countries. The study undertakes an empirical assessment of the main sources of youth unemployment in Africa. Based on panel data of 41 African countries covering the period 2000–2010, the study finds a demographic youth bulge and poor economic growth from both supply and demand sides of the market to be key drivers of youth unemployment in Africa. Employment-to-population ratio as a measure of country’s job creation ability and vulnerable employment as a proxy for informality are observed to have had a decreasing effect on youth unemployment. The empirical findings also suggest higher youth employment rates among females than males and a higher concentration in urban than rural areas. Investment in the high labour absorption sectors of agriculture and manufacturing is advocated as job creation strategies, along with population control measures to slow the growing youth population in Africa. High growth in the low employment sectors of mining and extractive industries could serve as resource generating avenues to promote investment in education and skill training, along with infrastructure to facilitate growth in high labour absorption sectors.
Keywords: Africa; economic growth; informal economy; labour markets; theories of unemployment; vulnerable workers; youth unemploymentJ 13; N37; N57; N67; O17; O55